The importance of water‐retaining features for biodiversity on artificial intertidal coastal defence structures. Issue 10 (22nd March 2013) - Firth, Louise B.; Thompson, Richard C.; White, Freya J.; Schofield, Meredith; Skov, Martin W.; Hoggart, Simon P. G.; Jackson, Juliette; Knights, Antony M.; Hawkins, Stephen J.; Defeo, Omar
Abstract Aim Artificial coastal defence structures are proliferating in response to rising and stormier seas. These structures provide habitat for many species but generally support lower biodiversity than natural habitats. This is primarily due to the absence of environmental heterogeneity and water‐retaining features on artificial structures. We compared the epibiotic communities associated with artificial coastal defence structures and natural habitats to ask the following questions: (1) is species richness on emergent substrata greater in natural than artificial habitats and is the magnitude of this difference greater at mid than upper tidal levels; (2) is species richness greater in rock pools than emergent substrata and is the magnitude of this difference greater in artificial than natural habitats; and (3) in artificial habitats, is species richness in rock pools greater at mid than upper tidal levels? Location British Isles. Methods Standard non‐destructive random sampling compared the effect of habitat type and tidal height on epibiota on natural rocky shores and artificial coastal defence structures. Results Natural emergent substrata supported greater species richness than artificial substrata. Species richness was greater at mid than upper tidal levels, particularly in artificial habitats. Rock pools supported greater species richness than emergent substrata, and this difference was more pronounced in artificial than natural habitats. Rock pools in artificial habitats supported greater species richness at mid than upper tidal levels. Main conclusions Artificial structures support lower biodiversity than natural habitats. This is primarily due to the lack of habitat heterogeneity in artificial habitats. Artificial structures can be modified to provide rock pools that promote biodiversity. The effect of rock pool creation will be more pronounced at mid than upper tidal levels. The challenge now is to establish at what tidal height the effect of pools becomes negligible and to determine the rock pool dimensions for optimum habitat enhancement.